The disease course in microscopic colitis may be influenced by hormonal factors - Klas Sjöberg; Lina Vigren; Marie-Rose Mellander; Izabella Janczewska; Hans Strid; Elisabeth Hultgren Hörnquist; Andreas Münch (BMC Gastroenterology)
Abstract Background Microscopic colitis (MC) is characterized by non-bloody, watery diarrhea predominantly in elderly women. Known risk factors are smoking, medication with NSAIDs, PPIs or SSRIs, while data on hormonal factors is sparse. The aim of the present study was to investigate whether hormonal factors that disrupt the sex hormonal balance could have an impact on the disease course in MC. Methods A questionnaire was distributed to 384 women with microscopic colitis (MC) (mean age 64 years, range 35–90) from five centers in Sweden about demographic aspects including age at diagnosis, disease duration, treatment, and polycystic ovary syndrome, endometriosis, bilateral oophorectomy, previous or ongoing medication with hormones or in vitro fertilization (IVF) in relation to the disease course. Results The association with smoking could be verified. In relation to the disease course the odds ratio (OR) was higher for celiac disease and oral contraceptives but lower for hormone replacement therapy but for the two latter non-significant. However, bilateral oophorectomy had a significantly lower OR (0.41, CI 0.19–0.86, p = 0.019). No other factors had any substantial impact on the disease course. Conclusion An association was verified with smoking. Celiac disease may be associated with more active disease. The observed lower OR for more active disease after bilateral oophorectomy is in line with a previously suggested association between the risk of MC and the hormonal balance. The exact mechanisms behind the hormonal effect on the disease course found in the present study are although still obscure.